Theodore Roosevelt Abroad - Thompson, J. Lee. author. aut Link
XV, 218 p.
Keywords: In a life full of momentous episodes, Theodore Roosevelt's fifteen-month post-presidential odyssey to Africa and Europe has never been given its due place. A tale of daring adventure, international celebrity, a friendship lost, and a political legacy transformed, Theodore Roosevelt Abroad is the first full account of this important time in history.